Lev Tolstoj in Edvard Munch v kontekstu dobe in kulture - Arhangel'skaja, Julija V. (Slavistična revija, 2015)
The article is devoted to comparative characteristics of some aspects of life and creative work of two outstanding representatives of the late 19th-20th-century European culture: Leo Tolstoy and Edvard Munch. The analysis deals with both the main themes of their creative work and stylistic features of their representation of basic concepts of culture of the epoch at the turn of the century.
Keywords: avtobiografski elementi; eksistencialna groza; ekspresionizem; Expressionism; kulturni koncept; Munch, Edvard, 1863-1944; norveška umetnost; norveški slikarji; realizem; ruska književnost; ruski pisatelji; Russian literature; tematologija; Tolstoj, Lev Nikolaevič, 1828-1910